(untitled) (Comprehensive Journal of Science, 2025)
This study, entitled "The Extent to Which Social Awareness is Affected by Social Modernization," aimed to determine the meaning of social awareness and the extent to which this awareness is affected by its surrounding environment, whether in terms of modernization or other social changes that occur in traditional societies. The research is of particular importance, namely, to determine the meaning of social awareness and the purpose of awareness, as well as to clarify the relationship between social awareness and the social modernization that any society undergoes. The research discusses the problem of being influenced by other concepts in sociology, including, but not limited to, social modernization, which has transformed traditional societies into modern societies, as seen in European modernization theories, and the transition of traditional societies into industrial societies. This is due to the influence of social awareness on what is happening around it in this environment. The researcher relied on the descriptive method and then the analytical method in order to highlight results that can be relied upon in the future. The researcher recommends the need to increase this type of research in order to know the extent to which social awareness is affected by its surrounding external and internal influences.